2012
DOI: 10.1073/pnas.1111943109
|View full text |Cite
|
Sign up to set email alerts
|

Selective esterase–ester pair for targeting small molecules with cellular specificity

Abstract: Small molecules are important tools to measure and modulate intracellular signaling pathways. A longstanding limitation for using chemical compounds in complex tissues has been the inability to target bioactive small molecules to a specific cell class. Here, we describe a generalizable esterase-ester pair capable of targeted delivery of small molecules to living cells and tissue with cellular specificity. We used fluorogenic molecules to rapidly identify a small ester masking motif that is stable to endogenous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
220
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 165 publications
(232 citation statements)
references
References 39 publications
12
220
0
Order By: Relevance
“…However, reliable targeting of a Ca 2+ -sensitive dye to selected cells in the live mammalian brain is usually achieved by visually guided intracellular loading, such as by maneuvering a micropipette (Kitamura et al, 2008), which impedes the study of large populations of cells of a single genetic class. Emerging chemical genetic methods may combine bulk loading of an indicator dye with genetic specificity (Tian et al, 2012). An existing alternative is to use one fluorescence color channel for detecting Ca 2+ signals across a broad population of indicator labeled cells and another color channel for identifying a subset of cells that express a fluorescent genetic marker (Kerlin et al, 2010; Nimmerjahn et al, 2004; Runyan et al, 2010).…”
Section: Neural Activity Indicatorsmentioning
confidence: 99%
“…However, reliable targeting of a Ca 2+ -sensitive dye to selected cells in the live mammalian brain is usually achieved by visually guided intracellular loading, such as by maneuvering a micropipette (Kitamura et al, 2008), which impedes the study of large populations of cells of a single genetic class. Emerging chemical genetic methods may combine bulk loading of an indicator dye with genetic specificity (Tian et al, 2012). An existing alternative is to use one fluorescence color channel for detecting Ca 2+ signals across a broad population of indicator labeled cells and another color channel for identifying a subset of cells that express a fluorescent genetic marker (Kerlin et al, 2010; Nimmerjahn et al, 2004; Runyan et al, 2010).…”
Section: Neural Activity Indicatorsmentioning
confidence: 99%
“…If optogenetic circuit analysis and RNA-seq identify a specific gene product that may perform an integral role in cellular signaling, therapeutics to inhibit or restore gene function or associated intracellular signaling modalities can then be designed. The technology for targeting genetically defined cells with small molecule drugs to restore normal functioning was demonstrated by a recent study from Tian et al (2012) that identified a specific esteresterase pair that could be used to deliver active small molecules to precisely defined cell types. The specific pair of porcine liver esterase (PLE) and a a-cyclopropyl ester was highly efficient at unmasking the small molecule and had negligible reactivity with endogenous esterases.…”
Section: Cell Type and Circuit Selective Small Molecule Pharmacothmentioning
confidence: 99%
“…The underlying principle of this strategy is to mask a small molecule drug by the attachment of a cleavable blocking functional group that renders it unreactive to endogenous cellular enzymes but is easily removed by a specific exogenous enzyme Tian et al, 2012). Cell type specificity is achieved by the expression of this exogenous enzymatic protein within a target cellular population where cleavage of the prodrug will occur and its therapeutic effect may be somewhat restricted.…”
Section: Cell Type and Circuit Selective Small Molecule Pharmacothmentioning
confidence: 99%
See 1 more Smart Citation
“…There is recent evidence that some serotypes of AAV may cross the BBB, and could therefore be delivered via intravenous injection [231], [232]. Newer, less invasive technologies to deliver small designer drugs or molecules have been proposed using conjugated nanoparticles or specific enzyme-substrate pairs, cleaved after crossing the BBB [233], [234], [235], [182]. In addition, toolboxes of cellular and regional mini-promoters in the brain are being defined [236] that can be utilized for targeting applications.…”
Section: Final Challenges -Human Therapeutic Applicationsmentioning
confidence: 99%